Persistent organic pollutants and the incidence of type 2 diabetes in the CARLA and KORA cohort studies. (August 2019) - Wolf, Kathrin; Bongaerts, Brenda W.C.; Schneider, Alexandra; Huth, Cornelia; Meisinger, Christa; Peters, Annette; Schneider, Andrea; Wittsiepe, Jürgen; Schramm, Karl-Werner; Greiser, Karin Halina; Hartwig, Saskia; Kluttig, Alexander; et al.
Abstract: Background: Associations between several persistent organic pollutants (POPs) and type 2 diabetes have been found in humans, but the relationship has rarely been investigated in the general population. The current nested case-control study examined internal exposure to polychlorinated biphenyls (PCB) and pesticides and the incidence of type 2 diabetes among participants of two population-based German cohort studies. Methods: We retrospectively selected 132 incident cases of type 2 diabetes and 264 age- and sex-matched controls from the CARdiovascular Living and Aging in Halle (CARLA) study (2002–2006, East Germany) and the Cooperative Health Research in the Region of Augsburg (KORA) study (1999–2001, South Germany) based on diabetes status at follow-up examinations in 2007–2010 and 2006–08, respectively (60% male, mean age 63 and 54 years). We assessed the association between baseline POP concentrations and incident diabetes by conditional logistic regression adjusted for cohort, BMI, cholesterol, alcohol, smoking, physical activity, and parental diabetes. Additionally, we examined effect modification by sex, obesity, parental diabetes and cohort. Results: In both cohorts, diabetes cases showed a higher BMI, a higher frequency of parental diabetes, and higher levels of POPs. We observed an increased chance for incident diabetes for PCB-138 and PCB-153 with an odds ratio (OR) of 1.50 (95%CI: 1.07–2.11) and 1.53 (1.15–2.04) per interquartile range increase in the respective POP. In addition, explorative results suggested higher OR for women and non-obese participants. Conclusions: Our results add to the evidence on diabetogenic effects of POPs in the general population, and warrant both policies to prevent human exposure to POPs and additional research on the adverse effects of more complex chemical mixtures. Highlights: Longitudinal studies on the association between POPs and diabetes in the general population are scarce. We investigated 132 incident cases of type 2 diabetes and 264 age- and sex-matched controls. Internal exposure to 3 polychlorinated biphenyls and 3 pesticides was determined at baseline. PCB-138 and PCB-153 were positively associated with incident type 2 diabetes. Women and non-obese participants indicated higher OR.